2015
DOI: 10.1614/wt-d-14-00109.1
|View full text |Cite
|
Sign up to set email alerts
|

Flumioxazin Tank-Mixtures with Six Herbicides for Annual Bluegrass (Poa annua) Control in Bermudagrass

Abstract: Flumioxazin is a protoporphyrinogen oxidase inhibitor with potential for POST annual bluegrass control and PRE smooth crabgrass control in bermudagrass. However, flumioxazin applications are often less effective in winter, compared with fall, because of reduced efficacy on mature annual bluegrass. The objective of this research was to evaluate tank-mixtures of flumioxazin with six other herbicide mechanisms of action for POST annual bluegrass control in late winter and residual smooth crabgrass control. Flumio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…Flessner et al (2013) reported that flumioxazin at 0.43 kg ai ha −1 controlled P. annua ≥95% up to a 2-tiller growth stage, but applications to plants with 4 to 6 tillers provided <50% control. Similar levels of POST P. annua control have been noted in field experiments with flumioxazin (Flessner et al 2013; Reed et al 2015). Moreover, there have been no reports of P. annua resistance to PPO inhibitors (Heap 2018), and flumioxazin offers an alternative mechanism of action for POST control of biotypes with resistance to other herbicides.…”
Section: Introductionsupporting
confidence: 71%
“…Flessner et al (2013) reported that flumioxazin at 0.43 kg ai ha −1 controlled P. annua ≥95% up to a 2-tiller growth stage, but applications to plants with 4 to 6 tillers provided <50% control. Similar levels of POST P. annua control have been noted in field experiments with flumioxazin (Flessner et al 2013; Reed et al 2015). Moreover, there have been no reports of P. annua resistance to PPO inhibitors (Heap 2018), and flumioxazin offers an alternative mechanism of action for POST control of biotypes with resistance to other herbicides.…”
Section: Introductionsupporting
confidence: 71%
“…The addition of flumioxazin to diquat, glufosinate, or glyphosate improved annual bluegrass control per day and final control at 84 DAT, but such improvement did not occur with oxadiazon admixture (Table 5). Reed et al (2015) also observed that flumioxazin tank-mixed with glyphosate was more effective than flumioxazin alone. Our results contrast with reports that combining contact-type modes of action herbicides with glyphosate could decrease weed control (Wehtje et al 2008, 2010).…”
Section: Resultsmentioning
confidence: 94%
“…However, control of certain weeds such as corn speedwell (Veronica arvensis L.), parsley-piert (Aphanes arvensis L.), and henbit (Lamium amplexicaule L.) with these herbicides has been inconsistent when they were investigated in bermudagrass and the herbicides have also injured dormant and semidormant bermudagrass (Derr and Serensits 2016;Johnson 1980). A large selection of herbicides other than hormone mimics, including acetolactate synthase inhibitors, photosystem II inhibitors, amino acid inhibitors, and cell wall biosynthesis inhibitors are routinely employed to control specific weed populations in dormant turfgrass (Brosnan et al 2012b;Johnson 1975bJohnson , 1984Reed et al 2015;Toler et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations